Serum Immunoglobulins, Pneumonia Risk, and Lung Function in Middle-Aged and Older Individuals: A Population-Based Cohort Study - Khan, Samer R.; Vanoverschelde, Anna; Lahousse, Lies; Peeters, Robin P.; van Hagen, P. Martin; Brusselle, Guy; Chaker, Layal; Dalm, Virgil A. S. H. (Frontiers in Immunology, 2022)
Introduction: Immunoglobulins (Igs) play a pivotal role in host defense and prevention of pneumonia. Aging influences serum Ig levels, but the association between Igs and pneumonia in community-dwelling older individuals remains unknown. We evaluated the association of serum IgA, IgG, and IgM with pneumonia and lung function in middle-aged and older individuals. Methods: We performed Cox and negative binomial regression analyses for the association of Igs with incident pneumonia and pneumonia-related mortality, and recurrent pneumonia respectively. We performed logistic regression analyses for the association between Igs and lung function values. Associations were adjusted for age, sex, smoking, comorbidities, and serum C-reactive protein. Results: We included 8,766 participants (median age 62.2 years, 57% women, median follow-up 9.8 years). Higher IgA (hazard ratio [HR]: 1.15; 95% confidence interval [95% CI]: 1.00-1.32) and IgG (HR: 1.13; 95% CI: 1.06-1.19) were associated with an increased pneumonia risk. Higher IgG was associated with an increased risk of pneumonia-related mortality (HR: 1.08; 95% CI: 1.01-1.16) and recurrent pneumonia (incidence rate ratio: 1.04; 95% CI: 1.00-1.09). Higher IgA and IgG were also associated with lower forced expiratory volume in one second (FEV1), lower forced vital capacity (FVC), and an increased odds of preserved ratio impaired spirometry (PRISm, i.e. FEV1 <80% and FEV1/FVC ratio ≥70%). No association was seen with an obstructive spirometry pattern. Discussion: Higher serum IgA and IgG levels were associated with pneumonia, pneumonia-related mortality, and PRISm in middle-aged and older individuals from the general population. Future studies should validate our findings and elucidate underlying pathophysiology.